ANCIENT EAST TITLES - Shaymardanov Azamat Zokirovich (Scholar Express Journal, 2021)
This article describes an analysis of the titles of rulers in the history of the statehood of Ancient Mesopotamia. An analysis of the epigraphic data reveals that in the city-states of Mesopotamia, the functions of religious and secular authority were gradually merged into the hands of a single ruler. Thus, the rulers of Mesopotamia assumed the positions of military chief, chief judge, and leading priest. In time, various titles were combined to form the title of "Ruler of the four countries of the world." The article covers the history of the emergence and evolution of titles in the history of the statehood of Ancient Mesopotamia
Keywords: Sumer; Arata; Kish; Nom